Faktor-faktor yang Mempengaruhi Audit Report Lag serta Dampaknya Terhadap Trading Volume Activity - Amrizal; Damayanti, Fina (Jurnal Ilmiah Wahana Akuntansi, 2022)
This study was conducted to analyze the factors that affect audit report lag and its impact on trading volume activity. This research is divided into 2 models, the first is used to find out how leverage, company size, and KAP size affect audit report lag and the second is used to find out how audit report lag influences trading volume activity. The population in this study are mining sector companies listed on the Indonesia Stock Exchange for the 2015-2020 period with a sample of 6 companies taken by purposive sampling method. This study uses multiple linear regression analysis and shows the results that in the first model leverage and KAP size have a negative effect on audit report lag, while company size has no effect on audit report lag. In the second model, audit report lag affects trading volume activity.